Drought risk reduction framework and practices: Contributing to the imp,ementation of the Hyogo framework for action. Preliminary version - Briceño, Silvano (Suecia :United Nations)
Understanding drought risk and vulnerability, main elements for a drought risk reduction framework and practices, policies and governance for drought, risk reduction, droght risk identification, impact assessment and early warning; networks and mechanisms to encourage the implementation of drought risk reduction projects and practices, global drought risk reduction paradigm, fostering practical drought risk reduction activities, concept of a global drought risk reduction and preparedness netwrk.
Contents, illustration, table, map
Col. Soc
Keywords: 1. CONSERVACIÓN-PROTECCIÓN 2. DROUGHT RISK REDUCTION-FRAMEWORK 3. NATURAL RESOURCES 4. SOCIOLOGY